Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2001
DOI: 10.1115/2001-gt-0178
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristics of a Flow Passage With Long Pin Fins and Improving Heat Transfer Coefficient by Adding Turbulence Promoters on a Endwall

Abstract: Pin fins are normally used for cooling the trailing edge region of a turbine, where their aspect ratio (height H/diameter D) is characteristically low. In small turbine vanes and blades, however, pin fins may also be located in the middle region of the airfoil. In this case, the aspect ratio can be quite large, usually obtaining values greater than 4. Heat transfer tests, which are conducted under atmospheric conditions for the cooling design of turbine vanes and blades, may overestimate the heat transfer coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, most research groups investigated basic and simple arrangements of pin-fin arrays with no additional devices to enhance heat transfer. Recently, Takeishi et al (9) investigated the overall heat transfer characteristics of pin fins with and without turbulence promoters (TP) on the endwall; they reported that TP enhance pin-fin heat transfer under actual engine conditions where fin efficiency becomes important because of the high heat transfer coefficient and low thermal conductivity of the superalloys used in the pin fins. The present study is an extension of an earlier study by Takeishi et al (9) to measure the local heat transfer coefficients, which are important in the cooling design of combustor liners and trailing edge sections of turbine vanes.…”
Section: Introductionmentioning
confidence: 99%
“…However, most research groups investigated basic and simple arrangements of pin-fin arrays with no additional devices to enhance heat transfer. Recently, Takeishi et al (9) investigated the overall heat transfer characteristics of pin fins with and without turbulence promoters (TP) on the endwall; they reported that TP enhance pin-fin heat transfer under actual engine conditions where fin efficiency becomes important because of the high heat transfer coefficient and low thermal conductivity of the superalloys used in the pin fins. The present study is an extension of an earlier study by Takeishi et al (9) to measure the local heat transfer coefficients, which are important in the cooling design of combustor liners and trailing edge sections of turbine vanes.…”
Section: Introductionmentioning
confidence: 99%